THE STATE AND PROSPECTS FOR THE DEVELOPMENT OF THE LOGISTICS SERVICES MARKET IN UKRAINE - YEVTUSHENKO, Victoria; SHUBA, Tetiana; TSVIATKO, Liliya; POPKOVA, Diana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article is devoted to the problem of researching the state and prospects for the development of the logistics services market in Ukraine. The importance of technological innovations in the field of transportation for the development of this field has been proven. The volumes of transported goods in Ukraine for 1995-2020 were analyzed. A comparative analysis of the state of logistics services in Ukraine and European countries was carried out. World trends in the development of logistics are revealed, namely: 3D visualization. This is a program that allows you to show the correct methods of storing cargo in vehicles. Blockchain. The logistics order monitoring system is being tested for the third year already. Robots and drones. Many companies have been testing delivery of pizza to end consumers with the help of robots. Unmanned transport and electric transport. 3D printing on a 3D printer. for many products, the need for transportation will disappear, it will be possible to send a 3D model by mail and print these products at home. The main obstacles to the development of logistics in Ukraine are highlighted, namely: the increase in the cost of fuel materials, high interest rates on loans, gaps in domestic legislation, high international requirements for rolling stock, non-compliance of the quality of roads with European standards, the density of the road network by 2-3 times lower than in the EU and the USA. It was concluded that one of the main problems of this area is the lack of a strategic development plan at the state level. This has led to a lack of understanding of trends in this area of the economy, which hinders medium- and long-term planning. Thus, a downturn in one or another sector of the economy can negatively affect the transport sector that serves it.